Diversity and distribution of plant-parasitic nematodes associated with watermelon, in northwest Morocco. (14th December 2021) - Laasli, Salah-Eddine; Lahlali, Rachid; Hajjaj, Badr; Saleh, Azzam; Dababat, Abdelfattah A.; Mokrini, Fouad
Abstract: Watermelon ( Citrullus lanatus ) fields in northwest Morocco's Molay Bousselham region were surveyed to study the distribution and occurrence of plant-parasitic nematodes. Eighteen nematode taxa were identified in soil and root samples collected from 24 watermelon plots. The most common plant-parasitic nematodes (PPN) identified were Meloidogyne ( M. javanica, M. incognita, M. arenaria and M. hapla ), Pratylenchus ( P. penetrans, P. thornei, and P. fallax ), Tylenchus, Helicotylenchus, Xiphinema and Ditylenchus genera. The diversity patterns of PPN were thoroughly assessed via calculating diversity indices. High species richness was recorded while significant differences were observed between the main locations based on the Shannon–Wiener index (H') and the Evenness (J). This description of PPN assemblages associated with watermelon fields in northwest Morocco provides fundamental information to design suitable nematode management strategies to reduce yield loss and benefit our food security.